Advancements in stability assessment: a novel method for impurity profiling in Montelukast and Fexofenadine dosage forms by RP-HPLC - Vikram S. Gharge; Vikas L. Mohite; Balasaheb S. Jadhav; Niteen D. Patil; Mangesh R. Jagdale; Deepti D. Masne; Jay A. Sonule (Discover Chemistry)
Abstract This study aims to develop and validate a specific, precise, and robust RP-HPLC method for the impurity profiling of Montelukast sodium and Fexofenadine in their combined tablet formulation. The method ensures accurate detection and quantification of impurities and degradation products, supporting quality control and stability testing. Chromatographic separation was achieved using a YMC Pack ODS column (150 × 4.6 mm, 3 μm) coupled with an Adhoc Scientific Ghost Terminator column (50 × 4.6 mm). A gradient elution was employed, starting at 0% mobile phase B, increasing to 20% at 15 min, 47% at 45 min, 70% at 50 min, 75% at 62 min, and 80% at 70 min, followed by re-equilibration to initial conditions by 80 min. Mobile phase A consisted of 0.01 M ammonium acetate buffer (pH 6.0): acetonitrile (80:20), and mobile phase B was acetonitrile: methanol (80:20). The flow rate was 1.0 mL/min, with a column temperature of 40 °C, sample temperature of 5 °C, and an injection volume of 15 µL. Detection was carried out at 240 nm using a UV/PDA detector. The method was validated for linearity, precision, accuracy, and stability-indicating capability. It showed excellent linearity (r² >0.999) from the LOQ to 150% of impurity limits. Recovery ranged from 80.0 to 120.0%, with %RSD below 5.0%, confirming high precision and accuracy. The method effectively identified known impurities, such as Fexofenadine-related compound A, Fexofenadine-related compound C, Montelukast sulfoxide, Montelukast cis, Montelukast ketone and Montelukast styrene and degradation products, proving its suitability for routine quality control and stability assessment in pharmaceutical manufacturing.